Glenoid Bone Reaction to All-Soft Suture Anchors Used for Shoulder Labral Repairs. (18th July 2018) - Tompane, T.; Carney, J.; Wu, W.W.; Nguyen-Ta, K.; Dewing, C.; Provencher, M.; McDonald, L.; Gibson, M.; LeClere, L.
Abstract : Background: All-soft suture anchors (ASSAs) are commonly used for shoulder labral repair and capsulorrhaphy in patients with shoulder instability. While these anchors may have some specific advantages over other types of suture anchors, little is known about the prevalence and time-dependence of bone cyst formation and tunnel expansion after implantation of ASSAs. The aim of this study was to quantify the proportions of cyst formation and tunnel expansion around ASSAs and to characterize and test for differences in abnormalities observed at different postoperative time points. Methods: Thirty patients who were treated with arthroscopic shoulder stabilization surgery with ASSAs (1.4 mm; JuggerKnot, Biomet) underwent a computed tomography (CT) scan of the operatively treated shoulder at 1 month (10 patients), 6 months (10 patients), or 12 months (10 patients) postoperatively. Demographic and operative data were collected, and CT scans were evaluated for cyst formation, tunnel expansion, and tunnel volume measured in cubic millimeters. Statistical analyses were performed to detect differences in these outcomes among the follow-up groups. All shoulders were stable at all time points of the study, and there were no incidents of recurrent instability during the study period. Results: Ninety-one suture anchors were evaluated in 30 patients. Tunnel expansion was identified in the large majority of patients in the 6-month and 12-month follow-up groups, with a significant increase in these proportions compared with the 1-month follow-up group (p = 0.002). Mean tunnel volumes also significantly increased over the study period (p < 0.001). The presence of cyst formation was negligible in all 3 follow-up cohorts. Conclusions: This study demonstrated low rates of cyst formation but a significantly increased tunnel volume 6 and 12 months after shoulder labral surgery with ASSAs. There was no association with the initial tunnel location. Additional well-controlled studies with longer follow-up are needed to identify potential associations among tunnel expansion, intraoperative technique, and clinical outcomes. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.